A randomized, double‐blind phase I/IIa study of intranasal glutathione in Parkinson's disease. Issue 12 (31st July 2015) - Mischley, Laurie K.; Leverenz, James B.; Lau, Richard C.; Polissar, Nayak L.; Neradilek, Moni B.; Samii, Ali; Standish, Leanna J.
ABSTRACT Background Depletion of reduced glutathione is associated with PD and glutathione augmentation has been proposed as a disease‐modifying strategy. The aim of this study was to determine the safety and tolerability of intranasal reduced glutathione in individuals with PD. Methods Thirty individuals with PD were randomized to either placebo (saline), 300 mg/day, or 600 mg/day of intranasal glutathione in three divided daily doses. Follow‐up visits included side effect screening of PD symptoms and cognition, blood chemistry, sinus irritation, and hyposmia. Tolerability was measured by frequency and severity of reported adverse events, compliance, and withdrawals from the study. Results After 3 months, there were no substantial differences between groups in the number of adverse events reported or observed among all safety measures assessed. All groups met tolerability criteria. Conclusions These data support the safety and tolerability of intranasal glutathione in this population. Pharmacokinetic and dose‐finding studies are warranted. © 2015 International Parkinson and Movement Disorder Society